Formation mechanism of the small-angle X-type strike-slip faults in deep basin and its controlling on hydrocarbon accumulation: a case study from the Tabei Uplift, Tarim Basin, NW China - Song, Xingguo; Chen, Shi; Zhang, Yintao; Xie, Zhou; Liang, Xinxin; Yang, Minghui; Zheng, Mingjun; Shi, Xukai (Frontiers in Earth Science, 2024)
In the central Tarim Basin, numerous hydrocarbon deposits were found along ultra-deep strike-slip faults, and its evolving progress and formation mechanism are research hotspots. The Paleozoic small-angle X-type strike-slip fault in the Tabei Uplift is the research subject in this article. Based on high-precision three-dimensional seismic data, three structural deformation layers were revealed: the rift system, weak strike-slip deformation and salt tectonics in the deep structural layer (Sinian-Middle Cambrian), the strong strike-slip deformation and karst-dissolution structure in the middle structural layer (Upper Cambrian-Middle Ordovician), and echelon normal faults in the shallow structural layer (Upper Ordovician-Carboniferous). The formation and evolution of strike-slip faults is jointly controlled by the distribution pattern of basement rift and the activities of surrounding orogenic belts, which can be divided into three stages. In the Middle to Late Cambrian, the initial subduction of the Paleo-Asian and Proto-Tethyan oceans precipitated the emergence of two sets of small-angle X-type strike-slip faults, striking NW and NE above the grooves of Precambrian rifts, influenced by local weak compressive stress. Affected by the closure of peripheral paleo-ocean, strike-slip faults deformed considerably in the Middle-Late Ordovician and were reactivated in the Silurian-Carboniferous, forming en-echelon normal faults in the shallow layer. The layered deformation structure of the strike-slip faults significantly affects the accumulation of hydrocarbons. The differential hydrocarbon enrichment of faults in the Tabei Uplift is collectively influenced by the distribution of source rocks and the migration of oil and gas. The topographical features of the Tabei Uplift, along with the distribution of strike-slip faults across tectonic units, have rendered the NE direction the preferential pathway for hydrocarbon migration. Additionally, impacted by the development of en echelon faults, the NE-trending faults offer superior conditions for hydrocarbon preservation and charging condition, compared to the NW-trending faults.